Training of management and establishment of sharia cooperatives (Baitul Maal Wat Tamwil) at Aisyiyah Percut Sei Tuan - Isra Hayati; Syahrul Amsari; Mutiah Khaira Sihotang; Ahmad Afandi (Community Empowerment, 2022)
This program was motivated by the lack of knowledge of the management and residents of Aisyiyah in establishing and managing the Sharia Cooperative at the Aisyiyah Percut Sei Tuan Branch. In addition, residents of Aisyiyah Percut Sei Tuan District still use usury-based cooperative savings and loan services. To improve knowledge and literacy, the purpose of this service is to provide management training on the establishment and management of sharia cooperatives, so that Sharia cooperatives can be formed at the Aisyiyah Percut Sei Tuan Branch. The stages of implementing this activity are preparation, training and evaluation of program success. From the results of the evaluation, the training participants gained an understanding and succeeded in forming a sharia cooperative under the name Tajri Aj Ma'a. In this activity, it was also decided the monthly contribution of cooperative members which must be paid.